The COVID-19 Economy: Building a Sustainable Future in the Shadow of a Crisis - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
As the global economy has continued to suffer from the ongoing COVID-19 pandemic, pressure has mounted for local and national economies to reopen despite the danger of disease. Unfortunately, before robust medical precautions are implemented, any such reopening will eventually prove futile, doing more harm than good. Areas which reopen must at the minimum have universal testing schemes and the capacity to identify and quarantine all arrivals from outside. Without this, new outbreaks will spring up without advance warning, forcing economies to close down again. Even if such mitigation measures are successfully adopted, latent fear will prevent many from returning to the patterns of everyday life until a vaccine is successfully developed and adopted. Until such a vaccine is produced, countries will have to introduce policies to shelter both people and businesses from the potential permanent impacts of a lengthy period of shutdown. The policies needed to respond effectively to the coronavirus, if successfully implemented and maintained, would yield the kinds of substantial advances in governance, social welfare, business development, and workforce adaptation that would move adopters well along the path of sustainable development and an inclusive embrace of the Fourth Industrial Revolution (4IR). For instance, governments would have the means to provide rapid economic support to their most vulnerable groups, while ensuring that key social services such as health and education were provided at a high and equitable standard. Groups once excluded from the halls of power could make their voices heard through advances in e-governance which include them in policy and decision-making processes. Advances in remote work and the sustainable design of cities could reduce inequalities and promote decent standards for employment while dramatically slashing pollution in urban spaces. Finally, the partnerships which have emerged between the public, private, and nonprofit sectors, if maintained, could develop into sources of strong, practical solutions to the full spectrum of challenges which will face society in the 21st century. Countries, in effect, have a binary choice between shielding their populations and preparing for their economic futures or maintaining status quo arrangements which will result in depression, unnecessary death, and lost competitiveness.
Keywords: 330